Analysis of endotracheal intubation-related judicial precedents in South Korea - Hye-Yeon Cho (Korean Society of Anesthesiologists, 2021)
Background Medical malpractice during endotracheal intubation can result in catastrophic complications. However, there are no reports on these severe complications in South Korea. We aimed to investigate the severe complications associated with endotracheal intubation occurring in South Korea, via medicolegal analysis. Methods We retrospectively analyzed the closed judicial precedents regarding complications related to endotracheal intubation lodged between January 1994 and June 2020, using the database of the Supreme Court of Korea. We collected clinical and judicial characteristics from the judgments and analyzed the medical malpractices related to endotracheal intubation. Results Of 220 potential cases, 63 were included in the final analysis. The most common event location was the operating room (n = 20, 31.7%). All but 3 cases were associated with significant permanent or more severe injury, including 31 deaths. The most common problems were failed or delayed intubation (n = 56, 88.9%). Supraglottic airway device was used in 5.2% (n = 3) cases of delayed or failed intubation. Fifty-one (81%) cases were ruled in favor of the plaintiff in the claims for damages, with a median payment of Korean Won 133,897,845 (38,000,000, 308,538,274). The most common malpractice recognized by the court was that of not attempting an alternative airway technique (n = 32, 50.8%), followed by violation of the duty of explanation (n = 10, 15.9%). Conclusions Our results could increase physicians’ awareness of the major complications related to endotracheal intubation and help ensure patient safety.